Integer Programming Approach In Bus Scheduling And Collection Optimization - Ismail, Zuhaimy; Ang, Pei Shan (Penerbit UTM Press, 2005)
This Paper Discusses The Current Practices Of Bus Services Within A Chosen Town Council. In This Service, The Driverâ€™s Schedule Has To Be Sorted Out As The Bus Timetable Involves Large Constraints And Requires Vast Amount Of Planning. Two Problems Were Studied, Namely The Overlapping Journey Which Resulted In Competition Among The Companyâ€™s Own Buses And The â€œunfairâ€? Distribution Of Tasks Among The Bus Crews. We Propose The Use Of Integer Programming Model To Determine Whether Adding An Interchange Would Improve Collections. Simple Rules Were Introduced In Rescheduling The Buses That Attempted To Minimize The Frequency Of Buses Departing From The Main Station (Larkin Terminal) At The Same Time. Using Excel Program With Visual Basic Application, We Develop A Scheduler System To Generate The Weekly Timetable For The Drivers. This Software Has Demonstrated Its Ability To Solve The Second Problem Of â€œunfairâ€? Distribution Of Duties. The Result Of The Integer Programming Model Shows That Adding An Interchange With Proper Allocation Of Buses Not Only Can Increase The Daily Collections But Also Improve The Trip Frequency As Well.